Wilson's disease associated with psychotic episode - case report (Research, Society and Development, 2022)
Wilson's Disease is a rare genetic disorder characterized by a failure in copper metabolism, which promotes copper deposition in both the liver and the brain, which can lead to serious complications if not diagnosed early and treated properly. The present case report exposes a psychotic episode in a patient previously diagnosed with Wilson's Disease and undergoing treatment, who exhibited failures in the follow-up of therapy associated with the excessive use of alcoholic beverages and especially of marijuana cigarettes since adolescence. Therefore, a bibliographical research on the themes was carried out and the discussion permeated about the possible correlations of these factors for the case described. It was concluded that the patient likely had an underdiagnosed psychiatric underlying illness that was exacerbated by accumulation of copper and drug use, causing the psychotic break to occur and thus later allowing for its diagnosis.